Sistem Pengawasan Bank Pasca kasus BLBI dalam Mendorong Reformasi Perbankan di Indonesia - Dinda Alifia Putri; Dativa Wilma Azali; Aprilia Puspitasari Putri Legiman (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The financial crisis in Indonesia during the late 1990s, particularly highlighted by the instance of the Bank Indonesia Liquidity Assistance (BLBI), emerged as a main subject of this discussion. This article investigates different facets concerning the crisis, covering everything from its origins to its effects on the economy and banking operations. Elements like corruption, flaws in financial oversight, and lenient monetary policies are the primary concerns of this crisis analysis. The conversation also encompasses an assessment of law enforcement's efficacy, victim protection, and actions to combat and tackle corruption. The social and political effects of the BLBI case are also highlighted, particularly regarding its impact on economic stability and investor trust. Banking reform and financial regulation emerge as key priorities in reaction to this case. Various critical assessments of the banking system, law enforcement, and legal reform are performed to develop suitable policy suggestions.